Cadmium Pollution Impact on the Bacterial Community Structure of Arable Soil and the Isolation of the Cadmium Resistant Bacteria - Yu, Xiaoxia; Zhao, JinTong; Liu, Xiaoqing; Sun, LiXin; Tian, Jian; Wu, Ningfeng (Frontiers in Microbiology, 2021)
Microorganisms play an important role in the remediation of cadmium pollution in the soil and their diversity can be affected by cadmium. In this study, the bacterial community in arable soil samples collected from two near geographical sites, with different degrees of cadmium pollution at three different seasons, were characterized using Illumina MiSeq sequencing. The result showed that cadmium is an important factor to affect the bacterial diversity and the microbial communities in the high cadmium polluted area (the site H) had significant differences compared with low cadmium polluted area (the site L). Especially, higher concentrations of Cd significantly increased the abundance of Proteobacteria and Gemmatimonas whereas decreased the abundance of Nitrospirae. Moreover, 42 Cd-resistant bacteria were isolated from six soil samples and evaluated for potential application in Cd bioremediation. Based on their Cd-MIC (minimum inhibitory concentration of Cd2+), Cd2+ removal rate and 16S rDNA gene sequence analyses, three Burkholderia sp. strains (ha-1, hj-2 and ho-3) showed very high tolerance to Cd (5 mM, 5 mM and 6 mM) and exhibited high Cd2+ removal rate (81.78%, 79.37% and 63.05%), six Bacillus sp. strains (151-5,151-6,151-13, 151-20,151-21) showed moderate tolerance to Cd (0.8 mM, 0.4 mM, 0.8 mM, 0.4 mM, 0.6 mM and 0.4 mM) but high Cd2+ removal rate (84.78%, 90.14%, 82.82%, 82.39%, 81.79% and 84.17%) . Those results indicated that Burkholderia sp. belonging to the phylum Proteobacteria and Bacillus sp. belonging to the phylum Fimicutes have developed a resistance for cadmium and may play an important role in Cd-contaminated soils. Our study provided baseline data for bacterial communities in cadmium polluted soils and concluded that Cd-resistant bacteria have potential for bioremediation of Cd-contaminated soils.